1995
DOI: 10.1021/bi00009a014
|View full text |Cite
|
Sign up to set email alerts
|

Internal Electron Transfer in Cytochrome c Oxidase from Rhodobacter sphaeroides

Abstract: Absorbance changes following CO dissociation by flash photolysis from mixed-valence aa3 cytochrome oxidase from Rhodobacter sphaeroides have been followed in the Soret and alpha regions. They reflect internal electron transfer in the partially reduced enzyme, and the kinetics of the reactions has been determined. As with the bovine enzyme, three kinetic phases are found with relaxation time constants at neutral pH of about 3 microseconds, 35 microseconds, and 1 ms. The first reaction phase represents electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
136
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(161 citation statements)
references
References 19 publications
21
136
4
Order By: Relevance
“…It is followed by electron transfer from heme a to Cu A at about 2 ϫ 10 4 s Ϫ1 . Similar studies have been carried out on other members of the terminal oxidase super family, including those from the bacterium Rhodobacter sphaeroides and cytochrome bo 3 from Escherichia coli (12,14,15), and the electron transfer events in these enzymes were detected on similar time scales. Recently, the rates and the extent of the electron transfer were questioned by Verkhovsky et al (16), who reported that an electron transfer event between the two hemes occurs on a time scale much faster than 100 ns, the limit of their instrumental resolution, and accounted for about 50% amplitude of the total amount of electron transfer from heme a 3 to heme a.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…It is followed by electron transfer from heme a to Cu A at about 2 ϫ 10 4 s Ϫ1 . Similar studies have been carried out on other members of the terminal oxidase super family, including those from the bacterium Rhodobacter sphaeroides and cytochrome bo 3 from Escherichia coli (12,14,15), and the electron transfer events in these enzymes were detected on similar time scales. Recently, the rates and the extent of the electron transfer were questioned by Verkhovsky et al (16), who reported that an electron transfer event between the two hemes occurs on a time scale much faster than 100 ns, the limit of their instrumental resolution, and accounted for about 50% amplitude of the total amount of electron transfer from heme a 3 to heme a.…”
supporting
confidence: 68%
“…The first phase is assigned to the electron transfer from heme a 3 to heme a, which occurs at a rate of ϳ3 ϫ 10 5 s Ϫ1 (8,12,13). It is followed by electron transfer from heme a to Cu A at about 2 ϫ 10 4 s Ϫ1 .…”
mentioning
confidence: 99%
“…This behavior was attributed to a titration of an internal proton donor/ acceptor within the K pathway (18,41). Because this maximum rate is slower than that observed with the membrane-reconstituted wild-type CytcO at pH 9.5, the effect of the membrane cannot be a simple pK a shift of this proton donor.…”
Section: Discussionmentioning
confidence: 91%
“…Results from earlier studies have shown that the rate of the PCET in detergent solution is pH dependent with a maximum value of ∼2;000 s −1 (τ ¼ 500 μs) at low pH (<7) (18). This behavior was attributed to a titration of an internal proton donor/ acceptor within the K pathway (18,41).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation